Lazarus. (2nd January 2019) - Molofsky, Merle
Abstract : This is a first-person narrative of an unmarried pregnant teenager who wants to name her baby Lazarus, because she knows the deep meaning of words, of names. She developed an interest in etymology after looking up her own name, Wanda, and creates a sense of identity. Is she pale or dark, or on the wane, or is she a wanderer, and will she let her inner light shine? She is pregnant because she never learned about dating or sex, and then … she met a man. She is interested in rocks, and fantasizes writing the lyrics of a rock song about rocks, and that eventually her son Lazarus would learn to play guitar and write the music.